Bacteriophage Ф S1 infection of Pseudomonas fluorescens planktonic cells versus biofilms - Sillankorva, Sanna (2004)
This communication focuses on the efficacy of a specific lytic phage, phage Ф S1, as a control agent of Pseudomonas fluorescens biofilms. The effect of phage infection temperature and the host growth temperature were evaluated. The results obtained showed that the phage infection process was temperature dependent and that the optimum temperature of infection of planktonic cells and biofilms was 26ºC. At this temperature, bacteriophage Ф S1, at a multiplicity of infection (MOI) of 0.5 infected both planktonic cells and biofilms causing a biomass reduction of about 85% in both cases.